Effects of piperine on intestinal permeation, pharmacodynamics and pharmacokinetics of insulin loaded chitosan coated solid lipid nanoparticles in rats - Indu Raghunath; Marina Koland; Suprit D. Saoji; Sarad Pawar Naik Bukke; N. Shridhar Deshpande; Varsha Augustin; Nilesh Rarokar; Chandrashekar Thalluri (Scientific Reports)
Abstract The oral administration of insulin offers significant clinical benefits due to its simplicity. This study evaluated piperine’s efficacy in improving insulin’s intestinal absorption in Wistar rats. Confocal microscopy demonstrated that prolonged retention of insulin-loaded chitosan-coated solid lipid nanoparticles (Ch-In-SLNs) on intestinal mucosa was due to chitosan’s mucoadhesive properties. These studies also revealed Ch-In-SLNs permeation in rat intestinal segments. Piperine enhanced the permeation of insulin-loaded nanoparticles, with more particles transported into deeper intestinal layers. The study assessed Ch-In-SLNs with piperine administered orally to diabetic rats. The formulated SLN’s effectiveness was evaluated in vivo in overnight-fasted Wistar rats. Male Wistar rats (n = 5) were divided into 8 groups, with the first as diabetic control, and others receiving various treatments, including blank SLN, oral insulin solution (25 IU/kg), subcutaneous (SC) insulin (5 IU/kg), and insulin nanoformulations (25 IU/kg and 50 IU/kg with and without piperine, respectively). Ch-In-SLN with piperine showed a statistically significant reduction (p < 0.05) in blood glucose levels in streptozotocin-induced (STZ) diabetic rats compared to SLNs without piperine and SC insulin. The Ch-In-SLN with piperine formulation demonstrated a noteworthy correlation between pharmacokinetics (PK) and pharmacodynamics (PD). This approach could replace traditional insulin injections and mitigate associated side effects, simplifying insulin therapy.